Weathering of crystalline marble at the Field Museum of Natural History, Chicago - Winkler, Erhard Maria; Kirchmayer, Martin (APT bulletin, 1991)
The coarse-grained crystalline Georgia marble that clads the exterior of the Field Museum of Natural History in Chicago was closely studied for weathering effects, specifically surface attack by dissolution and cracking of the column ribs. The three dominant weathering features observed on the columns are general surface reduction by dissolution; crumbling of marble beneath protective black crusts and deep cracking on the column ribs; and corners of the ashlar blocks. Loss of the marble surface was measured as a reduction against relatively unweathered grains of hornblende. A needle-pointed depth micrometer was used at over two hundred locations on the marble columns. The surface reduction-measured by comparing the height of patches of hornblende above the calcite, showed a maximum of 0.94 mm in the flutes for columns; the maximum erosion on the ribs, however, is 3.57 mm on the north side and 4.24 mm on the southwest side. In Chicago, about 1 meter of rain falls per year, and the typical rain acidity is near pH 4.3., which translates into an erosion rate of about 10 μm/1000 mm rain. Dissolution makes possible a rapid attack along the grain boundaries, which leads to microcracking. The presence of acidity in the water can accelerate the process considerably. Microcracks on the ribs tend to widen when stressed. Two types of fracture patterns can be distinguished on the weathered rib -- a single joint maximum pointing upward and a joint pattern influenced by the foliation. The direction of stress deviates 32° from the column axis. At the middle of the columns, the crack patterns exhibit tension fractures and crushed grains, as well as circumgranular fractures. Measurements taken at the bottom, middle, and top of the columns show a minimum stress on top, bulges in the center and a maximum stress at the bottom. The fracture analyses revealed that only 7% to 10% of all stress cracks are due to locked-in stress inherited from the geologic past that is triggered by weathering processes; the remaining 90% are caused by the load of the building on the columns. /// Le musée d'histoire naturelle Field de Chicago a fait l'objet d'une étude approfondie pour évaluer le vieillissement du marbre de Georgie à gros grain qui revêt sa façade. L'étude identifia trois formes dominantes de vieillissement sur les colonnes -- la perte de matière par dissolution de la surface, la friabilité du marbre sous les croûtes noires et la fissuration profonde des cannelures et des angles des blocs de pierre. La perte de matière fut mesurée par rapport à des grains de hornblende peu érodés et indiquant le niveau de la surface d'origine. Le décalage entre ces grains de hornblende et le calcite atteignait un maximum de 0,94mm au fond des cannelures et de 3,57mm pour leurs arêtes (côté nord) et de 4,24mm (côté sud-ouest). Chaque année, il tombe à Chicago environ 1 000 mm de pluie dont l'acidité moyenne est de pH 4,3 soit un taux d'érosion d'environ 10μm/1000mm de pluie. La dissolution entraîne une microfissuration en permettant une attaque du matériau entre ses particules, phénomène que peuvent accélérer ou amplifier les précipitations acides ou les efforts structuraux. On note deux types de fissures sur les arêtes exposées: des fissures simples orientées vers le haut et des réseaux complexes liés au litage de la pierre. A mi-hauteur des colonnes, les fissures indiquent une tension, un écrasement des grains et des fissures entre ceux-ci. Des mesures prises au bas, milieu et haut des colonnes indiquent des efforts minimes à la tête, un bombement au centre et un effort maximal à la base. L'analyse des fractures démontre que seulement 7-10% de celles d'origine structurale sont dues à des tensions internes d'origine géologique relâchée par le vieillissement, les 90% restants étant attribuables aux efforts structuraux imposés par le bâtiment aux colonnes.